Genetic Loss of Immunoglobulin A Does Not Influence Development of Alcoholic Steatohepatitis in Mice. (14th October 2016) - Inamine, Tatsuo; Yang, An‐Ming; Wang, Lirui; Lee, Kuei‐Chuan; Llorente, Cristina; Schnabl, Bernd
Abstract : Background: Chronic alcohol abuse is associated with intestinal dysbiosis and bacterial translocation. Translocated commensal bacteria contribute to alcoholic liver disease. Secretory immunoglobulin A (IgA) in the intestine binds bacteria and prevents bacterial translocation. Methods: To investigate the functional role of IgA in ethanol (EtOH)‐induced liver disease in mice, we subjected wild type (WT) and IgA‐deficient littermate mice to Lieber–DeCarli models of chronic EtOH administration and the model of chronic and binge EtOH feeding (the NIAAA model). Results: Chronic EtOH feeding increased systemic levels of IgA, while fecal IgA was reduced in C57BL/6 WT mice. WT and Iga −/− littermate mice showed similar liver injury, steatosis, and inflammation following 4 weeks of EtOH feeding or chronic and binge EtOH feeding. IgA deficiency did not affect intestinal absorption or hepatic metabolism of EtOH. Pretreatment with ampicillin elevated intestinal IgA in WT littermate mice. Despite increased intestinal IgA, WT littermate mice exhibited a similar degree of liver disease compared with Iga −/− mice after 7 weeks of EtOH feeding. Interestingly, bacterial translocation to mesenteric lymph nodes was increased in Iga −/− mice fed an isocaloric diet, but was the same after EtOH feeding relative to WT littermate mice. The absence of intestinal IgA was associated with increased intestinal and plasma IgM in Iga −/− mice after EtOH feeding. Conclusions: Our findings indicate that absence of IgA does not affect the development of alcoholic liver disease in mice. Loss of intestinal IgA is compensated by increased levels of intestinal IgM, which likely limits bacterial translocation after chronic EtOH administration. Abstract : Secretory immunoglobulin A (IgA) in the intestine binds bacteria and prevents bacterial translocation. Inamine et al. demonstrate that chronic ethanol feeding lowers intestinal IgA level in mice. However, genetic IgA deficiency is not sufficient to promote alcoholic liver disease in mice, because adaptations such as increased intestinal and plasma IgM, and possibly other yet unknown mechanisms compensate for the loss of IgA.